Pengaruh Jenis Media Perkecambahan dan Perlakuan Pra Perkecambahan terhadap Viabilitas Benih Mengkudu (Morinda citrifolia L.) dan Hubungannya dengan Sifat Dormansi Benih - Murniati, Endang; Suminar, Marlia (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
The experiment was conducted at Leuwikopo Lath House and Seed Science and Technology Laboratory Department of Agronomy, Bogor Agricultural University, Darmaga, Bogor, from March to June 2004. The objective of this research was to study the effects of germination substrate and pre germination treatment on the noni seed viability in relation to the seed dormancy. The research was arranged in the Randomized Complete Block Design with two factors. The first factor was germination substrates, consisted of sand, paddy charcoal and soil mixed with compost (1:1). The second factor was pre germination treatments, consisted of control, scarification, KNO3 1%, KNO3 2%, warm water (470C), combination of scarification and KNO3 1%, combination of scarification and KNO3 2%, combination of scarification and warm water (470C). This result showed that soil mixed with compost (1:1) was the best substrate for noni seed germination. Pre germination treatments as well as interaction between germination substrate and pre germination treatment had no significant effect on noni seed viability. Enforced dormancy occured on seeds which was germinated on paddy charcoal substrate. Key words : Morinda citrifolia seed, pre germination, paddy charcoal, enforced dormancy